Protection of collective rights and interests in arbitration - Dolganichev Vladimir Veniaminovich; Grubtsova Svetlana Pavlovna (SHS Web of Conferences, 2021)
Objective of the research: to identify the means of protection of collective interests, suitable for international commercial arbitration, based on models used in Russian procedural law and abroad. The research used both general scientific (analysis, synthesis, comparison, descriptive, formal-logical) and special legal (formal-legal, comparative-legal, historical-legal, method of legal modeling) methods. The work has resulted in a conclusion about the expansion of the use of collective rights and interests’ remedies in international commercial arbitration. In addition, conclusions are formulated on the admissibility in arbitration of such means of protection of collective rights and interests of procedural law as complicity, class actions, bankruptcy, protection of an indefinite range of persons and indirect claims. In particular, such a classic remedy of multiple persons as procedural complicity is often used in arbitration; on the other hand, rules are emerging on the possibility of using a class action to protect multiple persons in arbitration; the use of an indirect claim is also not restricted to arbitration, and it can be used subject to national law. The novelty of the research lies in the postulate of the impossibility in the modern legal process of using the institute of protection of an indefinite range of persons in arbitration due to the special nature of arbitration as a voluntary form of protection of rights and legitimate interests.